International financia management - Eun, Cheol S.; Resnick, Bruce G. (Tp. Hồ Chí Minh Kinh tế TP. Hồ Chí Minh, 2016)
International Financial Management is written based on two distinct parts: emphasis on the basics and emphasis on a managerial perspective.
Keywords: Tài chính - Ngân hàng